A Kantian foundation for welfare rights. (2nd January 2020) - Pinheiro Walla, Alice
ABSTRACT: In this article, I offer a foundation for the prima facie idea of a right to welfare based on a neglected aspect of Kant's legal theory: his account of equity rights ( aequitas, Billigkeit ) . I argue that these rights are not the same as the 'moral rights' of current literature, and that they arise as a consequence of systemic injustice. The contribution of this article is twofold: firstly, it provides an analysis and application of Kant's underanalysed and little understood discussion of equity; secondly, it offers an alternative to contemporary accounts of welfare rights as moral rights which can better account for their juridical nature as rights.